The effect of idea generation on innovative work behaviour among TVET teachers at vocational colleges in Malaysia. - Julia, Cliffton; Marinah, Awang; Mahaliza, Mansor (UNIMAS Publisher, 2025)
This study examines the effect of idea generation on Innovative Work Behaviour (IWB) among Technical and Vocational Education and Training (TVET) teachers in Malaysian vocational colleges. A quantitative, cross-sectional design was employed, and data were collected from 331 teachers using a validated questionnaire through stratified random sampling to ensure balanced representation across regions. Descriptive analysis demonstrated that both ideas were perceived at high levels. Pearson correlation analysis revealed a strong, positive relationship between idea generation and IWB, indicating that teachers who frequently engage in ideation are also more likely to demonstrate innovative teaching behaviours. A simple linear regression further confirmed that idea generation significantly predicts IWB. These findings highlight the critical role of cognitive creativity in shaping innovative educational practices. The study underscores the need for institutional strategies such as leadership support, collaborative cultures, and professional development to promote idea generation in vocational education. The results contribute to the theoretical understanding of IWB and provide practical insights for educational policymakers. Future research should explore additional organisational and contextual factors that may influence innovation in teaching and learning.